Voltage Control in the Future Power Transmission Systems - Qin, Nan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on the formulation of a multi-stage optimization framework for the Danish power system, taking into account the real operational cost, the voltage constraints and the uncertainty associated to the forecasting errors of the wind power. It describes in detail the implementation of this framework into a simulation platform and its validation in real-world applications. The book especially focuses on automatic voltage control systems and on methods to handle uncertainty in them. All in all, it provides readers with a comprehensive overview of power system optimization and future trends in power system operation.  .
Introduction -- Load Flow Calculation -- Numerical Optimization -- Danish AVC System.-  Implementation -- Case Studies -- Fallback Scheme -- Conclusions.
Keywords: Electric power production; Control engineering; Electrical Power Engineering; Mechanical Power Engineering; Control and Systems Theory